Innovation and Knowledge Creativity in Regional Development: Combination of Different Missions - Lina Sun (Forest Chemicals Review)
Maximizing socio-economic contribution of innovation system demands a better comprehension of the systems which are made up of the networks of coordination in and out of these contemporary institutes. The existence of different innovation institutes augments regional competitiveness, which demonstrates the combination of teaching, research as well as innovation as missions from different institutes involved in socio-economic engagement. The greater socio-economic role they can play in fostering regional growth, the more necessary it is for the integration of its internal teaching, research and innovation coordination systems. While research on regional innovation has identified the important role that these institutes play in collaboratively generating innovative knowledge, how teaching and research activities trigger knowledge production in the institutes and the combined importance of three factors in knowledge spillovers essential to regional competitiveness still remains relatively unexplored. We analyze the necessity of saving diversity in the missions to explore effective and sustainable approaches to their engagement in regional development.